Oligarchical Populism; The Analysis of President Joko Widodo's Political Communication - Andi, Andi; Sujoko, Anang; Sobari, Wawan (Technium Social Sciences Journal, 2021)
There are two perspectives toward the appearance of Joko Widodo (Jokowi) to a national political field. The first impression represents optimism towards political decentralization in Indonesia is by addressing Jokowi as a populist figure who can be a politician from a regional area to a capital city. Then, the second impression represents the oligarchy thesis, which is called the rise of Jokowi to a national political landscape because of oligarchies firmly rooted in Indonesia. This study aims to analyze Jokowi’s political communication through populism and oligarchy framework, and the domination of both. This study uses the transformative critical paradigm with the critical discourse analysis (CDA) Teun. A van Dijk’s model as method. The communication of Jokowi’s politics related to corruption eradication, investment escalation, and freedom of expression are analyzed critically by using that method. The result reveals that Jokowi is under two political concepts which contrast to one another, namely populism and oligarchy. These concepts make Jokowi a weak figure who fights the oligarchy’s will. Consequently, Jokowi is not sincerely fighting the KPK’s weakening strategy, inconsistency in developing investment, and the non-sense statement about freedom of expression. In this case, Jokowi (a populist) is being in the oligarchs’ co-optation or ‘oligarchical populism’.